If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(4c + -1) + -3 = 7c + 9 Reorder the terms: 3(-1 + 4c) + -3 = 7c + 9 (-1 * 3 + 4c * 3) + -3 = 7c + 9 (-3 + 12c) + -3 = 7c + 9 Reorder the terms: -3 + -3 + 12c = 7c + 9 Combine like terms: -3 + -3 = -6 -6 + 12c = 7c + 9 Reorder the terms: -6 + 12c = 9 + 7c Solving -6 + 12c = 9 + 7c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '-7c' to each side of the equation. -6 + 12c + -7c = 9 + 7c + -7c Combine like terms: 12c + -7c = 5c -6 + 5c = 9 + 7c + -7c Combine like terms: 7c + -7c = 0 -6 + 5c = 9 + 0 -6 + 5c = 9 Add '6' to each side of the equation. -6 + 6 + 5c = 9 + 6 Combine like terms: -6 + 6 = 0 0 + 5c = 9 + 6 5c = 9 + 6 Combine like terms: 9 + 6 = 15 5c = 15 Divide each side by '5'. c = 3 Simplifying c = 3
| Y=-7.5x+11 | | 36m+107-3m=36 | | (x-4)+(2x-7)=0 | | 8m=-3m+1 | | V-2x+3y-z=8 | | 0=-15-3y-4x | | 5p-9=2p+21 | | (X+8)=(4X-28) | | 2.5(2+z)=5(z+2.5) | | y=1.5-1 | | A=6F+4g | | 5x-2(7x-1)=14x | | 4Y^2+x^2=4 | | 3a-2=5 | | 4Y^2+x^2= | | 7(X-5)=71 | | 35x+7=11x+4 | | 4z=6z+2 | | Logx=2.4 | | 2x-4y+z=0 | | 8(2z-5)=4n+8 | | 3-8+2x=11+6x | | p/20=8/4 | | [-2+6x]+3=59 | | 5.79x-3.14y=-13.54 | | 3(2-0.9q)+(-1.3h-4)= | | -3(4t-4)+6t=5t-9 | | x^2+8+14=0 | | 4x-10+2x=8 | | f+g=f+h | | x^2+814=0 | | x^2+8+14= |